2018
DOI: 10.1103/physrevb.97.035421
|View full text |Cite
|
Sign up to set email alerts
|

Phonon hydrodynamics for nanoscale heat transport at ordinary temperatures

Abstract: The classical Fourier's law fails in extremely small and ultrafast heat conduction even at ordinary temperatures due to strong thermodynamic nonequilibrium effects. In this work, a macroscopic phonon hydrodynamic equation beyond Fourier's law with a relaxation term and nonlocal terms is derived through a perturbation expansion to the phonon Boltzmann equation around a four-moment nonequilibrium solution. The temperature jump and heat flux tangential retardant boundary conditions are developed based on the Maxw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 82 publications
(193 reference statements)
2
91
0
Order By: Relevance
“…First, they are valid for general phonondispersion relations; previous mesoscopic approaches for hydrodynamic thermal transport replaced these with power-law or linear-isotropic relations [14][15][16], which are reasonable approximations only at cryogenic temperatures. In addition, we take into account the full collision matrix, refining other models derived from the LBTE in the SMA [70] or in the Callaway approximation [72]. It is worth noting that Hardy & Albers [20] derived a set of mesoscopic equations from the LBTE that may be regarded as the generalization of the Guyer-Krumhansl equation for a general phonon dispersion relation (i.e.…”
Section: Viscous Heat Equationsmentioning
confidence: 99%
“…First, they are valid for general phonondispersion relations; previous mesoscopic approaches for hydrodynamic thermal transport replaced these with power-law or linear-isotropic relations [14][15][16], which are reasonable approximations only at cryogenic temperatures. In addition, we take into account the full collision matrix, refining other models derived from the LBTE in the SMA [70] or in the Callaway approximation [72]. It is worth noting that Hardy & Albers [20] derived a set of mesoscopic equations from the LBTE that may be regarded as the generalization of the Guyer-Krumhansl equation for a general phonon dispersion relation (i.e.…”
Section: Viscous Heat Equationsmentioning
confidence: 99%
“…In summary, larger values of C lead to less resistance to heat flow and thus to greater values of the thermal Figure 4: The influence of non-uniform slip coefficients C on the normalised ETC k eff /k of a square nanowire (φ = 1). Lines correspond to the ETC computed using the slip coefficient in (22). The cases β = 0, β = 2, and β = −0.9 correspond slip coefficients that are constant, increasing towards a corner, and decreasing towards a corner.…”
Section: Resultsmentioning
confidence: 99%
“…3.4, the large-Kn behaviour of the ETC for a constant slip coefficient in the case of a square nanowire is given by k eff /k ∼ (C equiv /2)Kn −1 . By inserting the slip coefficient (22) into (20), performing the integration, and equating the result to (C equiv /2)Kn −1 , we find an equivalent slip constant given by…”
Section: Resultsmentioning
confidence: 99%
“…Hence a form of the jump conditions given in [1, Ch. 2, eqs [25][26][27] is easily retrieved. The momentum condition (9b) highlights a problem with this derivation form.…”
Section: Jump Conditions At the Interfacementioning
confidence: 99%
“…The Maxwell-Cattaneo equation gives rise to the hyperbolic or relativistic heat equation, which describes heat propagation with finite speed. Although the Guyer-Krumhansl equation was originally derived for situations with extremely low temperatures, recent studies have shown that it may be accurate at much higher temperatures [25]. It has been used to successfully predict the size dependence of the thermal conductivity in nanowires for temperatures ranging from 1 to 350 K [12,11], a feature that cannot be captured using Fourier's law.…”
Section: Non-fourier Heat Transfermentioning
confidence: 99%